Socio-economic influence on mental health in post-war jaffna society a multivariate statistical review - Elankumaran, C. (university of Jaffna, 2020)
This study focuses on the socio-economic influences on the nature of mental health in post war Jaffna society, prior to Covid-19 pandemic. This is a follow Soc re subjected to investigation. The general measures of Mental Health include "Confidence on Quality of Life" and "Pain or Discomfort in Daily Life". Specific measures formulated were in dimensions, "Psychological Symptoms". "Physiological Symptoms", "Psycho-Physiological Symptoms" and "Ambiguous Symptoms". Socio-Economic factors used were "Occupation", "Income", "Expenditure", and "Food Consumption". Exploratory dataanalysis, Cluster analysis, Canonical Discriminant analysis and Logistic regression analysis were adopted to extract the results in this study. We found that there are adverse effects among the majority (78%) of the couples in post-war scenario. In-depth analysis in terms of Psychological issues, shows that more than half of the couples feel low spirit, about half suffered by poor memory, less than one-fourth feels loneliness, about half of the husbands and more than one-fourth of the wives feels restless, about one-third of the couples feel failure of their expectations, about one-fifth of the couples feel wondering for un-worthwhile life, about two-fifth of the couples suffered by un-happiness, and about two-fifth of the couples are suffered by sleepless conditions. Similar outcomes were also found in the other three dimensions. Hence, our study confirms that the Jaffna society has been suffering in mental health in the post-war scenario. Investigation for the influence of socio-economic factors on the dimension 'Psychological Symptoms' reveals that the occupational level and family income have direct impacts on the psychological wellness of the people. The inherent causes of this effects were found to be the loss of employment or under employment due to the consequences of war and displacements. More than half of the couples have experienced psychological disorders due to economic reasons. We also found little more than one-fourth of the wives have been suffering by physiological, psycho-physiological and ambiguous symptoms due to socio-economic reasons. This nature of effects in such three types of mental health disorders due to economic reasons is found in more than three-tenth among the husbands. It is confirmed among the husbands due to the fact that their changing occupational levels, changing work environment which was hostile to normal life patterns and changing food consumption patterns stimulated such effects.
Keywords: Socio-economic status; Psychological-physiological-ambiguous symptoms; Exploratory data analysis; Cluster analysis; Logistic regression analysis